Building in mid-nineteenth Century Halifax: The Case of George Lang - Buggey, Susan (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
An important element in the construction of the nineteenth century cityscape was the "master builder," who in Halifax emerged in the late 1850s and early 1860s, and who significantly changed the role of builders from, primarily, artisans in particular trades to contractors with capacity to meet the needs of large scale construction. They were men who undertook building on a scale sufficient to employ a continuous workforce and who usually carried out all aspects of a contract. One such man was George Lang, a Scottish mason, who in the period 1858 to 1865 contracted for construction of a number of major buildings in growing Halifax. The study of one such "master builder" provides some insight into the study of the cityscape, though much work remains on the inter-relationship of builder, artisan, and architect, as well as the role of legislation, the nature and supply of material, the economics of the building process and the general relationship of buildings to the urban environment.